PENERAPAN METODE KINESIO TAPPING UNTUK MENGURANGI NYERI PUNGGUNG BAWAH PADA IBU HAMIL TRIMESTER III - Maria Menda; Susanti (Universitas Batam, 2023)
Low back pain is common in pregnancy with reported incidence varying from approximately 50% in the UK and Scandinavia to close to 70% in Australia. Factors that cause back pain in pregnant women are weight gain, rapid changes in posture, previous back pain, repeated stretching, many children, high levels of relaxin. One of the midwives' efforts to reduce the intensity of low back pain is by providing kinesio tapping. Research Objectives To provide midwifery care to pregnant women in a comprehensive manner by applying the kinesio tapping method to reduce lower back pain in third trimester pregnant women. The type of research used in the preparation of practice reports is descriptive research using a case study method. The research was conducted at the Tanjung Balai Karimun Health Center in March 2023. The subjects used in this case study were third trimester pregnant women with low back pain problems. This method is used 3 to 5 days of use depending on conditions. Kinesio Tapping can be applied as a complementary therapy in midwifery care services in pregnancies with back pain, especially in the third trimester